Jejunalni Meckelov divertikel kot izvor hude krvavitve pri mladostniku - Mahne, Stanislav (Zdravniški vestnik, 2003)
Background. Meckel' s diverticulum is the most frequent congenital anomaly of the small intestine, which mostly causes no health disturbances; however, it can cause serious complications: bleeding inflammation with perforation and peritonitis, or intestinal obstruction. Patients and methods. A case of major lowe gastrointestinal tract bleeding in a previously healthy 18 years old boyis presented. Endoscopic examinations did not reveal the source of bleeding. The technetium 99 scintiscan demonstrated ectopic gastric mucosa in the lower abdomen, and barium small bowel studies depicted a saccular dilatation in the mid jejunum, with mucosal folds alike those in the stomach. At operation in jejunum, 85 cm distally of the Treitz ligament, a quite large diverticulum was found. We resected it within healthy margins and made an end-to-end anastomosis of the jejunum. Conclusions. Meckel's diverticulum is the commonest cause of a major gastrointestinal bleeding in children. The diagnosis is confirmed on scintiscan, as ectopic gastric mucosa is usually present in the diverticulum. In the adults bleeding is rare; more often intestinal obstruction and diverticulitis are encountered. The removal of a non-diseased incidentally found Meckel's diverticulum is recommended mostly ininfants and young people, considering also local and general conditions of the patient.
Keywords: Adolescenca; Adolescence; Diagnosis; Etiology; Gastrointestinal Hemorrhage; Gastrointestinalna krvavitev; Jejunal Diseases; Jejunalne bolezni; Meckelov divertikel; Meckel'S Diverticulum; Surgery